Methane adsorption in the low–middle-matured Neoproterozoic Xiamaling marine shale in Zhangjiakou, Hebei. Issue 5 (4th July 2018) - Xu, L. W.; Liu, L. F.; Jiang, Z. X.; Chen, L.; Wang, Y.
ABSTRACT: The adsorption capacity of high–over-matured shale has been widely investigated, but the adsorption capacity and the main factors influencing low–middle-matured, type II kerogen-containing, and organic-rich marine shale have been rarely explored. This research conducts organic geochemistry, mineralogical composition, adsorption isotherm tests to reveal the adsorption and main influencing factors of the different geochemistry characteristics, mineralogical compositions, temperature and pressure conditions of the low–middle-matured Neoproterozoic Xiamaling marine shale in Zhangjiakou, Hebei. The investigated shale is in a low–middle maturity stage, contains type II kerogen and is rich in organic matter. The results show that the total organic carbon (TOC) content of the Xiamaling shale is positively correlated with the methane adsorption capacity, which is the most important influencing factor on the adsorptive property of shale. The methane adsorption capacity first decreases to the minimum value as the temperature reaches 360°C equivalent Ro (EqRo = 1.0%), then increases and reaches the maximum value at 620°C (EqRo = 3.28%) and finally decreases again as the temperature rises at the last simulation stage. The mineral components exhibit an insignificant influence on the methane absorbability because of organic-matter coatings. The TOC-normalised methane adsorption capacity is positively correlated with the illite–smectite and clay-mineral contents but shows no significant correlation with brittle minerals, such as quartz. Soluble organic matter and kerogen caused the methane dissolution and adsorbtion, respectively. The strong dissolution property of the soluble organic matter is the most important cause of the larger adsorption capacity of the original shale compared with that of the residual samples. Moreover, the methane adsorption capacity of the Xiamaling shale decreases with increasing temperature, and increases with pressure below the critical pressure but decreases exceeding the critical pressure.